A Survey on Twitter Sentiment Analysis - Rahman, Eriq-Ur; Sarma, Rituparna; Sinha, Rajesh; Pradhan, Adarsh; Sinha, P (International Journal of Computer Sciences and Engineering, 2025)
Twitter sentiment analysis offers organizations an ability to monitor public feeling towards the products and events related to them in real time. Public and private opinion about a wide variety of subjects are expressed and spread continually via numerous tweets. It offers organizations a fast and more effective way to analyze customer’s perspectives towards the success in the market place. Sentiment analysis is an approach to be used to computationally measure customer’s perceptions to a vast extent. This is a survey on the design of a sentiment analysis. After extraction of a vast amount of tweets, it classifies perspectives of customers via tweets into positive and negative sentiments. Which is obtained after classifying the data by using classification approaches like for example Bayes Naïve, Linear Regression, etc